A Socio-Cultural Value Embedded in English Textbook Seventh Grade Students of Junior High School - Yanti, Sarli; Tahrun, Tahrun; Mulyadi, Mulyadi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aimed to identify the central issues of socio-cultural values, understand how these socio-cultural values are implemented, and determine the dominance of specific socio-cultural values represented in the 7th grade English textbook titled